Spatial distribution, structural characterization and weathering of tarmats along the west coast of Qatar - S. Veerasingam (9648980) (2020)
Oil pollution resulting from natural and anthropogenic activities in the Arabian Gulf as well as oil residue in the form of tarmat (TM) deposited on the coast is a major environmental concern. The spatial distribution, chemical composition and weathering pattern of tarmat along the west coast of Qatar has been assessed based on the TM samples collected from 12 coastal regions. The range of TM distribution is 0–104 g m−1 with an average value of 9.25 g m−1. Though the current TM level is thirty-fold lesser than that was found during 1993–1997 (average 290 g m−1), the distribution pattern is similar. The results of ATR-FTIR spectroscopy indicate that aromatic compounds are higher in the north (N) coast TMs than those found in the northwest (NW) and southwest (SW) coasts, and Carbonyl Index values indicate that TM of NW coast is highly weathered compared to those found in the N and SW coasts. Other Information Published in: Marine Pollution Bulletin License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.marpolbul.2020.111486